Solid electrolyte based on single ion conductor polymer and preparation method thereof

By introducing fluorine-containing lithium salt monomers and electron-absorbing groups into the single-ion polymer solid electrolyte, and using ultraviolet curing technology and crosslinking agents, a high-density chemical crosslinking grid structure is formed, which solves the problem of low conductivity of existing electrolytes, and achieves efficient transmission of lithium ions and optimization of electrochemical performance.

CN119695270APending Publication Date: 2025-03-25SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411941258.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The ionic conductivity of existing single-ion polymer solid electrolytes is relatively low and it is difficult to meet the practical application needs.

Method used

By introducing strong electron absorption groups into benzenesulfonamide, a fluorine-containing lithium salt monomer is synthesized, and a group with electron withdrawal effect is added to the anionic structure to enhance the degree of center delocalization and reduce the affinity for lithium ions, thereby promoting the dissociation and transportation of lithium ions. At the same time, ultraviolet curing technology and crosslinking agents are used to prepare in-situ crosslinked single-ion conductor polymer solid electrolytes to form a high-density chemical crosslinking grid structure to promote uniform dispersion and efficient transmission of lithium ions.

Benefits of technology

The ionic conductivity of single-ion conductor polymer solid electrolyte is significantly improved, achieving efficient transmission of lithium ions and optimization of electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695270A_ABST
    Figure CN119695270A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte based on a single ion conductor polymer and a preparation method thereof, the structural formula of the solid electrolyte is shown as a formula (V): # imgabs0 #, n is 1, and R is any one of-F,-CF3 or-OCF3. According to the polymer solid electrolyte, a group with an obvious electron withdrawing effect is added to an anion structure of a lithium salt monomer, so that the center delocalization degree can be enhanced, the affinity to lithium ions is reduced, dissociation and transportation of the lithium ions are promoted, and excellent ionic conductivity is realized; namely, the negative charge density of an anion part can be effectively increased by introducing an electron withdrawing group with a high electron accepting characteristic, so that the interaction force between the anion part and lithium ions is weakened, and then the in-situ cross-linked single-ion conductor polymer solid electrolyte is prepared by adding a cross-linking agent and adopting an ultraviolet curing technology. The high-density chemical cross-linked grid structure promotes uniform dispersion of lithium ions in the electrolyte, so that the conductivity of the lithium ions is improved, and efficient transmission is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of development of energy storage solid electrolytes and relates to a single ion conductor polymer solid electrolyte and a preparation method thereof. Background Art

[0002] In recent years, polymer solid electrolytes have developed rapidly in the field of lithium metal batteries, mainly due to their multiple significant advantages, including significantly improved safety, superior energy density and gradually reduced costs. These characteristics make polymer solid electrolytes a strong candidate to replace traditional liquid electrolytes, which is of great significance for promoting the advancement of lithium metal battery technology. However, polymer solid electrolytes also face a major challenge in their development, namely their high crystallinity characteristics. High crystallinity limits the migration ability of polymer chains, which in turn hinders the effective transmission of lithium ions. This limitation leads to the generally low ionic conductivity of polymer solid electrolytes, usually only 10^-6 to 10^-8 S cm^-1 at 25°C, which is far below the level required for practical applications. In order to improve the ionic conductivity of polymer solid electrolytes, researchers have begun to explore new methods for constructing single-ion polymer solid electrolytes. In this electrolyte, the stability of the electrolyte can be improved to a certain extent by introducing specific lithium salt monomers. In recent years, various methods for constructing lithium salt monomers using different groups have been reported in relevant public patent literature, which have improved the performance of polymer solid electrolytes to a certain extent.

[0003] Nevertheless, the ionic conductivity of single-ion polymer solid electrolytes is still not ideal and there is still a certain gap from practical application. Therefore, how to further optimize the structure of single-ion polymer solid electrolytes and improve their ionic conductivity is still a key issue to be solved in the current lithium metal battery field. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a single ion conductor polymer solid electrolyte and a preparation method thereof, thereby solving the technical problem of low conductivity of polymer solid electrolyte in the prior art.

[0005] The present invention is achieved through the following technical solutions: A single ion conductor polymer solid electrolyte, the structural formula of which is shown in formula (V):

[0006] In the formula, n is 1, and R is any one of -F, -CF3 or -OCF3.

[0007] The above-mentioned method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: S1: Under ice bath conditions, carbon disulfide and 2-bromopropionic acid are added to tert-butyl mercaptan to obtain an intermediate product A after reaction. The structural formula of the intermediate product A is formula (I): ; In an ice bath and under nitrogen protection, polyethylene glycol monomethyl ether is reacted with 4-vinylbenzyl chloride to obtain an intermediate product B, the structural formula of the intermediate product B is formula (II): ; Styrenesulfonyl chloride is added to anhydrous oxygen-free acetonitrile, and fluorine-containing benzenesulfonamide, 4-dimethylaminopyridine and triethylamine are added, and the mixture is stirred under ice bath conditions. After the reaction is completed, the reaction product is reacted with anhydrous lithium hydroxide to obtain a fluorine-containing lithium salt monomer. The structural formula of the fluorine-containing lithium salt monomer is formula (III):

[0008] Wherein, R is any one of -F, -CF3 or -OCF3; S2: adding the fluorine-containing lithium salt monomer, the intermediate product B, azobisisobutyronitrile and the intermediate product A into N,N'-dimethylformamide, stirring for reaction, and obtaining a fluorine-containing single ion polymer lithium salt; S3: adding the fluorine-containing single-ion polymer lithium salt, PEO and a cross-linking agent into N,N'-dimethylformamide, stirring until completely dissolved, and initiating polymerization by ultraviolet light to obtain the single-ion conductor polymer solid electrolyte.

[0009] Preferably, in terms of mass fractions, the ratio of tert-butyl mercaptan to carbon disulfide to 2-bromopropionic acid is 3:(1-10):(5-15).

[0010] Preferably, in terms of mass fractions, the ratio of the polyethylene glycol monomethyl ether to 4-vinylbenzyl chloride is (2-5):(1-3).

[0011] Preferably, the ratio of styrenesulfonyl chloride to fluorine-containing benzenesulfonamide is (14-20):(8-10) in parts by mass.

[0012] Preferably, the fluorine-containing benzenesulfonamide is any one of 4-fluorobenzenesulfonamide, 4-trifluoromethoxy-benzenesulfonamide and 4-trifluoromethyl-benzenesulfonamide.

[0013] Preferably, in terms of mass fractions, the ratio of the fluorine-containing lithium salt monomer, the intermediate product B, azobisisobutyronitrile and the intermediate product A is (40-50):(40-50):1:(15-20).

[0014] Preferably, the fluorine-containing single-ion polymer lithium salt accounts for 4% to 10% of the mass of PEO.

[0015] Preferably, in the process of initiating polymerization by ultraviolet light, the wavelength of the light source is 400-100 nm, and the light intensity is 0.2-0.4 wm -2 , the lighting time is 3~6h.

[0016] A lithium metal battery comprises the above-mentioned single ion conductor polymer solid electrolyte.

[0017] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a single-ion conductor polymer solid electrolyte. A fluorine-containing lithium salt monomer is obtained by introducing a strong electron-absorbing group into benzenesulfonamide. A group with a significant electron-withdrawing effect is added to the anion structure of the lithium salt monomer to enhance the degree of central delocalization and reduce the affinity for lithium ions, thereby promoting the dissociation and transport of lithium ions and achieving excellent ion conductivity. That is, the invention can effectively increase the negative charge density of the anion part by introducing an electron-withdrawing group with high electron-accepting characteristics, thereby weakening the interaction force between the anion part and the lithium ions. Subsequently, an in-situ cross-linked single-ion conductor polymer solid electrolyte is prepared by adding a cross-linking agent and adopting ultraviolet light curing technology. The high-density chemical cross-linking grid structure promotes the uniform dispersion of lithium ions in the electrolyte, thereby improving the conductivity of lithium ions and achieving efficient transmission.

[0018] In addition, the present invention also discloses a preparation method of the above-mentioned single-ion conductor polymer solid electrolyte, wherein, in terms of mass fractions, the ratio of tert-butyl mercaptan to carbon disulfide to 2-bromopropionic acid is 3:(1~10):(5~15), which can effectively ensure the preparation of the target product RAFT agent.

[0019] Furthermore, the ratio of polyethylene glycol monomethyl ether to 4-vinylbenzyl chloride is (2-1):(3-1) by weight, which can effectively ensure the synthesis of polymer lithium salt branches.

[0020] Furthermore, in terms of mass fractions, the ratio of styrenesulfonyl chloride to fluorine-containing benzenesulfonamide is (30-20):(20-10), which can effectively ensure the synthesis of fluorine-containing lithium salt monomers.

[0021] Furthermore, the fluorine-containing benzenesulfonamide is any one of 4-fluorobenzenesulfonamide, 4-trifluoromethoxy-benzenesulfonamide and 4-trifluoromethyl-benzenesulfonamide, so that three fluorine-containing lithium salt monomers with different end groups can be prepared.

[0022] Furthermore, the ratio of the fluorine-containing lithium salt monomer, the intermediate product B, azobisisobutyronitrile and the intermediate product A is (40-50):(40-50):1:(15-20) in terms of mass fractions, so that a single ion conductor polymer lithium salt can be prepared.

[0023] Furthermore, the fluorine-containing single-ion polymer lithium salt accounts for 4% to 10% of the mass of PEO, which can be used to prepare a single-ion conductor polymer solid electrolyte.

[0024] Furthermore, in the process of initiating polymerization by ultraviolet light, the wavelength of the light source is 400-100 nm, and the light intensity is 0.2-0.4 wm -2 The illumination time is 3 to 6 h, which can make the reaction generate single ion conductor polymer lithium salt. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 A reaction process diagram of a method for preparing a single ion conductor polymer solid electrolyte in the present invention; Figure 2 PFV synthesized in Examples 1 to 3 of the present invention 750 PF3OV 750 PF3V 750 1H NMR spectrum of Figure 3 The electrochemical impedance spectra (a) of polymer solid electrolytes prepared using different single-ion polymer lithium salts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 at 25° C. and the ionic conductivities (b) at different temperatures are shown. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0028] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0029] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions).

[0030] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0031] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0032] The present invention discloses a single ion conductor polymer solid electrolyte, the structural formula of which is shown in formula (V):

[0033] In the formula, n is 1, and R is any one of -F, -CF3 or -OCF3.

[0034] The ionic conductivity of the single ion conductor polymer solid electrolyte at 25°C is (1.5~2.0)×10 -5 Scm -1 , the ionic conductivity at 60℃ is (1.1~1.5)×10 -4 S cm -1 .

[0035] In addition, if Figure 1 As shown, the present invention also provides a method for preparing a single ion conductor polymer solid electrolyte, comprising the following steps: Step 1, according to the mass fraction, 3 parts of tert-butyl mercaptan are added to 5 parts of ultrapure water and stirred evenly; a 40% to 50% mass fraction of NaOH aqueous solution is dropped into the above mixed solution and fully stirred, and the system is stirred to make the pH value of the system 8 to 12; acetone (20.0 mL to 50.0 mL) is slowly added to obtain a colorless transparent solution, stirred for 0.5 to 1.0 h and cooled to room temperature; the above reaction is transferred to an ice bath, 1 to 10 parts of carbon disulfide, 5 to 15 parts of 2-bromopropionic acid and a 40% to 50% mass fraction of NaOH aqueous solution are added, and NaOH is added here to make the reaction process more thorough, and the reaction temperature is controlled not to exceed 60°C. After the reaction stops exothermic, the ice bath is removed and the reaction is continued at room temperature for 24 to 48 hours; after the reaction is completed, 5 to 10 parts of concentrated hydrochloric acid are added and the temperature is controlled to be less than 10°C to obtain a yellow oil layer and stirred until solidified, washed with a large amount of ultrapure water, and vacuum dried for 12 to 15 hours to obtain a yellow solid to obtain the target product, which is recorded as BCSPA. The reaction equation in this process is shown in Figure 1 The structural formula of the product BCSPA is shown in (I):

[0036] Step 2: Slowly add 1-5 parts of sodium hydride to 5-10 parts of dry tetrahydrofuran under nitrogen purge, add 2-5 parts of polyethylene glycol monomethyl ether with a molecular weight of 750 and 1-3 parts of 4-vinylbenzyl chloride under ice bath condition, and react for 12-14 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water for extraction, filter, and obtain a light yellow target product, recorded as VBMPEG. 750 . In this process, the nitrogen atmosphere can prevent oxygen from participating in the reaction or causing oxidation of the reactants. Sodium hydride (NaH) is a strong base, often used to generate organometallic compounds or deprotonation reactions. In dry tetrahydrofuran, it can better exert its alkaline effect. Ice bath conditions are used to control the reaction temperature to prevent excessive reaction or unnecessary side reactions. Rotary evaporation can remove the solvent tetrahydrofuran, and extraction and filtration can remove unreacted reactants and by-products. The reaction equation in this process is shown in Figure 1 The B type in the product VBMPEG 750 The structural formula is shown in (II):

[0037] Step 3, add 5 parts of thionyl chloride (SOCl2), 2 parts of sodium 4-styrenesulfonate and 6 parts of anhydrous N,N'-dimethylformamide (DMF) into a flask, stir in an ice bath for 0.5~5h, stir at room temperature for 6~10h, and then freeze, filter and evaporate to obtain styrenesulfonyl chloride (SSC). Add fluorinated benzenesulfonamide, 4-dimethylaminopyridine and triethylamine to anhydrous oxygen-free acetonitrile (ACN), wherein the ratio of styrenesulfonyl chloride to fluorinated benzenesulfonamide, 4-dimethylaminopyridine and triethylamine is (14~20):(8~10):1:(10~15) by mass, and stir for 0.5~3h under ice bath. After the reaction is completed, add an appropriate amount of anhydrous magnesium sulfate to the mixed solution, dry, filter, evaporate, remove dichloromethane, and obtain a yellow viscous product. Finally, the product and anhydrous lithium hydroxide (mass ratio is 20:(13~19)) are dissolved in an appropriate amount of dichloromethane (DCM), and stirred at room temperature for 24~36 hours to form a light yellow solution, thereby obtaining the target product, a fluorine-containing lithium salt monomer.

[0038] The fluorinated benzenesulfonamide in this step includes any one of 4-fluorobenzenesulfonamide, 4-trifluoromethoxy-benzenesulfonamide and 4-trifluoromethyl-benzenesulfonamide. In this process, 4-dimethylamino-pyridine (DMAP) is used as a catalyst for the acylation reaction to promote the reaction. Triethylamine (Et3N) is used as a base to neutralize the acid produced during the reaction and also helps to increase the solubility of the reactants. The anhydrous and oxygen-free conditions are to prevent the reactants from being oxidized or hydrolyzed. The reaction equation in this process is shown in Figure 1 The structural formula of the fluorine-containing lithium salt monomer is shown in formula (III):

[0039] Wherein, R is any one of -F, -CF3 or -OCF3.

[0040] Step 4, according to the weight percentage, the fluorine-containing lithium salt monomer and VBMPEG 750 , azobisisobutyronitrile, and BCSPA are added to 5 parts of N,N'-dimethylformamide at a ratio of (40~50):(40~50):1:(15~20), and stirred at 55~75℃ for 18~24h. After the reaction time is over, the solution is poured into a large amount of anhydrous ether at -20℃ to precipitate the target product. The obtained product is placed in a vacuum drying oven at 40~60℃ and vacuum dried for 6~12h to obtain a fluorinated single ion polymer lithium salt (theoretical molecular weight 3000~5000). The reaction equation in this process is shown in Figure 1The structural formula of the fluorine-containing lithium salt monomer is shown in Formula (IV):

[0041] Step 5, mixing the fluorine-containing single ion polymer lithium salt with polyethylene oxide (PEO), wherein the fluorine-containing single ion polymer lithium salt accounts for 4% to 10% of the mass of polyethylene oxide, and adding the crosslinking agent trimethylolpropane triacrylate into a round-bottom flask containing 1 to 2 parts of N,N-dimethylformamide (DMF), heating and stirring until the mixture is completely dissolved. Then pour the above mixture into a polytetrafluoroethylene plate, initiate polymerization by ultraviolet light, and polymerize in the ultraviolet light layer, the light source band is 400 to 100 nm, and the light intensity is 0.2 to 0.4 wm -2 , the illumination time is 3~6 h, and finally, vacuum drying is performed at 50~70℃ for 36~48h to obtain a solid electrolyte based on a single ion conductor polymer. The reaction equation in this process is shown in Figure 1 The component structure of the solid electrolyte based on the single ion conductor polymer is shown in Formula (V):

[0042] In this process, firstly, fluorine-containing single-ion polymer lithium salt, PEO and cross-linking agent TMPTA are added to a round-bottom flask containing 1-2 parts of DMF, and heated and stirred until the mixture is completely dissolved. At this stage, it is necessary to ensure that all reactants are fully dissolved to form a uniform solution, which provides a good foundation for the subsequent polymerization reaction. Then the above mixture is poured into a polytetrafluoroethylene plate, and the polymerization is initiated by ultraviolet light. Under the irradiation of ultraviolet light, the acrylate groups in TMPTA undergo polymerization to form a cross-linked network. At the same time, PEO and fluorine-containing single-ion polymer lithium salt also interact to a certain extent to form an interpenetrating network structure. At this stage, the intensity and irradiation time of ultraviolet light need to be controlled to ensure that the polymerization reaction is fully carried out. Finally, the main purpose of vacuum drying at 50-70°C for 36-48h is to remove the residual DMF solvent and unreacted monomers, so that the solid electrolyte forms a stable structure. At the same time, appropriate temperature and drying time also help to improve the performance and stability of the solid electrolyte. In this process, due to the introduction of fluorine-containing single-ion polymer lithium salt, a channel for lithium ion migration is provided, so that the solid electrolyte has a higher ionic conductivity. PEO, as a polymer matrix, forms an interpenetrating network structure with fluorinated single-ion polymer lithium salts, while TMPTA, as a cross-linking agent, forms a cross-linked network, which together improves the mechanical strength and toughness of the solid electrolyte. At the same time, the high-density chemical cross-linked grid structure promotes the uniform dispersion of lithium ions in the electrolyte, thereby improving the conductivity of lithium ions and achieving efficient transmission. The residual solvent and monomer are removed by vacuum drying, so that the solid electrolyte has good stability and service life.

[0043] The present invention synthesizes a fluorinated single-ion polymer electrolyte by a reversible addition-fragmentation chain transfer polymerization method, and prepares a PEO-based single-ion conductive polymer solid electrolyte by photoinitiation, that is, the present invention synthesizes a fluorine-containing lithium salt monomer by introducing a strong electron absorption group into benzenesulfonamide. Subsequently, an in-situ cross-linked single-ion PEO-based solid electrolyte membrane is prepared by adding a cross-linking agent trimethylolpropane triacrylate (TMPTA) and using ultraviolet light curing technology. The introduction of electron-withdrawing groups with high electron acceptance characteristics can effectively increase the negative charge density of the anion part, thereby weakening its interaction force with lithium ions. The high-density chemically cross-linked grid structure promotes the uniform dispersion of lithium ions in the electrolyte, thereby improving the conductivity of lithium ions and achieving efficient transmission.

[0044] That is, the present invention adopts a reversible addition-fragmentation chain transfer polymerization method to synthesize a fluorinated single-ion polymer electrolyte with enhanced conductivity, and adds a strong electron-withdrawing group. By introducing a group with a strong electron-withdrawing effect or a high dielectric constant into the anion group, the center delocalization range can be expanded, and its affinity with lithium ions can be reduced, thereby promoting the dissociation and transmission of lithium ions. On this basis, a cross-linking agent is appropriately added to cross-link independent polymers with each other, construct a controllable network structure, and then create more ion transmission paths to obtain more excellent ion conductivity. The prepared solid polymer exhibits excellent electrochemical properties at room temperature.

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0046] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0047] Example 1 A method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: Step 1, add 36.0g of tert-butyl mercaptan to 60.0mL of ultrapure water and stir evenly; drip a 50% by mass NaOH aqueous solution into the above mixed solution and stir thoroughly; slowly add acetone (20.0mL) to obtain a colorless transparent solution, stir for 0.5h and cool to room temperature; transfer the above reaction to an ice bath, add 34.0g of carbon disulfide, 62.0g of 2-bromopropionic acid and a 50% by mass NaOH aqueous solution, control the reaction temperature not to exceed 60°C, remove the ice bath after the reaction stops exothermic, and continue the reaction at room temperature for 24h; after the reaction is completed, add 60.0mL of concentrated hydrochloric acid and control the temperature to be less than 10°C to obtain a yellow oil layer and stir until solidified, wash with a large amount of ultrapure water, and vacuum dry for 12h to obtain a yellow solid, recorded as BCSPA.

[0048] Step 2: Slowly add 3.0 g of sodium hydride to 150.0 mL of dried tetrahydrofuran under nitrogen purge, add 23.63 g of polyethylene glycol monomethyl ether with a molecular weight of 750 and 10.82 g of 4-vinylbenzyl chloride under ice bath conditions, and react for 12 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water for extraction and filtration to obtain a light yellow target product, recorded as VBMPEG. 750 .

[0049] Step 3, stir for 0.5h under ice bath conditions, add 60.0mL thionyl chloride, 20.6g sodium 4-styrenesulfonate and 60.0mL anhydrous N,N'-dimethylformamide into the flask, stir for 0.5h under ice bath conditions and continue to stir for 6h at room temperature, after which, freeze, filter and evaporate to obtain styrenesulfonyl chloride (SSC). Add 7.9g 4-fluorobenzenesulfonamide, 0.6g 4-dimethylaminopyridine and 10.1g triethylamine reagent to anhydrous oxygen-free acetonitrile and stir for 0.5h under ice bath conditions. After the reaction is completed, add an appropriate amount of anhydrous magnesium sulfate to the above mixed solution, dry, filter, evaporate, remove dichloromethane, and obtain a yellow viscous product. Finally, dissolve it in an appropriate amount of dichloromethane with anhydrous lithium hydroxide (20:19), stir at room temperature for 24h to form a light yellow solution, marked as SSFPSILi, i.e., fluorine-containing lithium salt monomer.

[0050] Step 4, take 0.7g of SSFPSILi solution and 0.9g of VBMPEG 750 15.0 mg of azobisisobutyronitrile and 196.0 mg of BCSPA were added to 20 mL of N,N'-dimethylformamide, and stirred at 75 ° C for 18 hours. After the reaction time, the solution was poured into a large amount of anhydrous ether (-20 ° C) to precipitate the target product. The obtained product was placed in a vacuum drying oven at 40 ° C and dried for 6 hours to obtain a fluorine-containing single-ion polymer lithium salt, recorded as PFV 750 .

[0051] Step 5: Add the above fluorinated single ion polymer lithium salt, PEO and crosslinker trimethylolpropane triacrylate (addition amount is 4 wt%) into 20 mL N,N'-dimethylformamide, and heat and stir until the mixture is completely dissolved. Then pour the above mixture into a polytetrafluoroethylene plate, prepare a polymer solid electrolyte film by ultraviolet light-induced polymerization, and dry it in a vacuum oven at 70°C for 48 hours to obtain a solid electrolyte based on a single ion conductor polymer. The sample is labeled PFV 750 -4%.

[0052] Example 2 A method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: Step 1, add 36.0g of tert-butyl mercaptan to 60.0mL of ultrapure water and stir evenly; drip a 50% by mass NaOH aqueous solution into the above mixed solution and stir thoroughly; slowly add acetone (20.0mL) to obtain a colorless transparent solution, stir for 0.5h and cool to room temperature; transfer the above reaction to an ice bath, add 34.0g of carbon disulfide, 62.0g of 2-bromopropionic acid and a 50% by mass NaOH aqueous solution, control the reaction temperature not to exceed 60°C, remove the ice bath after the reaction stops exothermic, and continue the reaction at room temperature for 24h; after the reaction is completed, add 60.0mL of concentrated hydrochloric acid and control the temperature to be less than 10°C to obtain a yellow oil layer and stir until solidified, wash with a large amount of ultrapure water, and vacuum dry for 12h to obtain a yellow solid, recorded as BCSPA.

[0053] Step 2: Slowly add 3.0 g of sodium hydride to 150.0 mL of dried tetrahydrofuran under nitrogen purge, add 23.63 g of polyethylene glycol monomethyl ether with a molecular weight of 750 and 10.82 g of 4-vinylbenzyl chloride under ice bath conditions, and react for 12 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water to extract and filter to obtain a light yellow target product, recorded as VBMPEG. 750 .

[0054] Step 3, stir under ice bath conditions for 0.5h, add 60.0mL thionyl chloride, 20.6g sodium 4-styrenesulfonate and 60.0mL anhydrous N,N'-dimethylformamide into the flask, stir under ice bath conditions for 0.5h and continue stirring at room temperature for 6h, after which, freeze, filter and evaporate to obtain styrenesulfonyl chloride (SSC). Add 7.9g 4-trifluoromethoxy-benzenesulfonamide, 0.6g 4-dimethylaminopyridine and 10.1g triethylamine reagent to anhydrous oxygen-free acetonitrile and stir under ice bath conditions for 0.5h. After the reaction is completed, add an appropriate amount of anhydrous magnesium sulfate to the above mixed solution, dry, filter, evaporate, remove dichloromethane, and obtain a yellow viscous product. Finally, dissolve it in an appropriate amount of dichloromethane with anhydrous lithium hydroxide (20:19), stir at room temperature for 24h to form a light yellow solution, marked as SSTFMOPSILi, i.e., fluorine-containing lithium salt monomer.

[0055] Step 4, take 0.7g of SSTFMOPSILi solution and 0.9g of VBMPEG 750 15.0 mg of azobisisobutyronitrile and 196.0 mg of BCSPA were added to 20 mL of N,N'-dimethylformamide, and stirred at 75 ° C for 18 hours. After the reaction time, the solution was poured into a large amount of anhydrous ether (-20 ° C) to precipitate the target product. The obtained product was placed in a vacuum drying oven at 40 ° C and dried for 6 hours to obtain a lithium single ion conductor polymer lithium salt, recorded as PF3OV 750 .

[0056] Step 5: Add the above-mentioned fluorinated single-ion polymer lithium salt, PEO and cross-linking agent trimethylolpropane triacrylate (addition amount is 4 wt%) to 20 mL of N,N'-dimethylformamide, and heat and stir until the mixture is completely dissolved. Then pour the above mixture into a polytetrafluoroethylene plate, prepare a polymer solid electrolyte film by ultraviolet light-induced polymerization, and dry it in a vacuum oven at 70°C for 48 hours to obtain a solid electrolyte based on a single-ion conductor polymer. The sample is labeled PF3OV 750 -4%.

[0057] Example 3 A method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: Step 1, add 36.0g of tert-butyl mercaptan to 60.0mL of ultrapure water and stir evenly; drip a 50% by mass NaOH aqueous solution into the above mixed solution and stir thoroughly; slowly add acetone (20.0mL) to obtain a colorless transparent solution, stir for 0.5h and cool to room temperature; transfer the above reaction to an ice bath, add 34.0g of carbon disulfide, 62.0g of 2-bromopropionic acid and a 50% by mass NaOH aqueous solution, control the reaction temperature not to exceed 60°C, remove the ice bath after the reaction stops exothermic, and continue the reaction at room temperature for 24h; after the reaction is completed, add 60.0mL of concentrated hydrochloric acid and control the temperature to be less than 10°C to obtain a yellow oil layer and stir until solidified, wash with a large amount of ultrapure water, and vacuum dry for 12h to obtain a yellow solid, recorded as BCSPA.

[0058] Step 2: Slowly add 3.0 g of sodium hydride to 150.0 mL of dried tetrahydrofuran under nitrogen purge, add 23.63 g of polyethylene glycol monomethyl ether with a molecular weight of 750 and 10.82 g of 4-vinylbenzyl chloride under ice bath conditions, and react for 12 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water to extract and filter to obtain a light yellow target product, recorded as VBMPEG. 750 .

[0059] Step 3, stir under ice bath conditions for 0.5h, add 60.0mL thionyl chloride, 20.6g sodium 4-styrenesulfonate and 60.0mL anhydrous N,N'-dimethylformamide into the flask, stir under ice bath conditions for 0.5h and continue stirring at room temperature for 6h, respectively. After completion, freeze, filter and evaporate to obtain styrenesulfonyl chloride (SSC). Add 7.9g 4-trifluoromethyl-benzenesulfonamide, 0.6g 4-dimethylaminopyridine and 10.1g triethylamine reagent to anhydrous oxygen-free acetonitrile and stir under ice bath conditions for 0.5h. After the reaction is completed, add an appropriate amount of anhydrous magnesium sulfate to the above mixed solution, dry, filter, evaporate, remove dichloromethane, and obtain a yellow viscous product. Finally, dissolve it with anhydrous lithium hydroxide (20:19) in an appropriate amount of dichloromethane, stir at room temperature for 24h to form a light yellow solution, marked as SSTFMPSILi, i.e., fluorine-containing lithium salt monomer.

[0060] Step 4, take 0.7g of the above solution and 0.9g of VBMPEG 750 15.0 mg of azobisisobutyronitrile and 196.0 mg of BCSPA were added to 20 mL of N,N'-dimethylformamide, and stirred at 75 ° C for 18 hours. After the reaction time, the solution was poured into a large amount of anhydrous ether (-20 ° C) to precipitate the target product. The obtained product was placed in a vacuum drying oven at 40 ° C and dried for 6 hours to obtain a lithium single ion conductor polymer lithium salt, recorded as PF3V 750 .

[0061] Step 5: Add the above-mentioned fluorinated single-ion polymer lithium salt, PEO and cross-linking agent trimethylolpropane triacrylate (addition amount is 4 wt%) to 20 mL of N,N'-dimethylformamide, and heat and stir until the mixture is completely dissolved. Then pour the above mixture into a polytetrafluoroethylene plate, prepare a polymer solid electrolyte film by ultraviolet light-induced polymerization, and dry it in a vacuum oven at 70°C for 48 hours to obtain a solid electrolyte based on a single-ion conductor polymer. The sample is labeled PF3V 750 -4%.

[0062] Comparative Example 1 The difference from Example 1 is that the polymer lithium salt end group does not contain a strong electron-withdrawing fluorine-containing group. The prepared sample is marked as PV 750 -4%.

[0063] Figure 2 PFV synthesized in Examples 1 to 3 of the present invention 750 PF3OV 750 PF3V 750 1H NMR spectrum of the fluorinated lithium single ion polymer 1 In the H NMR spectrum, the peak intensity of hydrogen on the -CH=CH2 group belonging to the molecular structure of the fluorinated lithium salt monomer was significantly weakened; while a broad peak belonging to -CH2- appeared in the displacement range of 1.91-0.69 ppm, further proving the breakage of the C=C bond. In addition, the chemical shift at 4.43 ppm was attributed to VBMPEG 750 The peak with a chemical shift of 3.68-3.09 ppm for hydrogen in CCH2O is VBMPEG 750 The peaks of hydrogen in OCH2CH2 and OCH3 indicate that three fluorine-containing lithium single-ion polymer lithium salts were successfully prepared.

[0064] Figure 3 Electrochemical impedance spectra (a) of polymer solid electrolytes prepared using different single-ion polymer lithium salts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 at 25°C and ionic conductivities (b) at different temperatures are shown in FIG. Figure 3 As shown in Figure a, PFV 750 -4%,PF3OV 750 -4% and PF3V 750 -4% and the room temperature ionic conductivity is 1.54×10 -5 , 1.89×10 -5 and 2.04×10 -5 S cm -1 , and PV 750 -4% of 1.37×10 -5 S cm -1Both have been improved. This is due to the rational design of the structure of the lithium salt monomer and the introduction of electron-withdrawing groups, which increase the delocalization of negative charges and reduce the interaction between anionic groups and lithium ions; in addition, the introduction of fluorine elements reduces the crystallinity of PEO in the polymer solid electrolyte film to a certain extent. The synergistic effect of the two promotes the migration of lithium ions and improves the ionic conductivity of the polymer solid electrolyte film. Furthermore, the effect of temperature changes on the ionic conductivity of the sample was also studied, and the results are shown in Figure 3 As shown in Figure b, at 60°C, PFV 750 -4%,PF3OV 750 -4% and PF3V 750 -4% ionic conductivity is 1.17×10 -4 , 1.36×10 -4 and 1.51×10 -4 S cm -1 The ionic conductivity of the polymer solid electrolyte shows a linear correlation with temperature. The activation energy is calculated and the results are shown in Table 1. As shown in Table 1, PF3V 750 The activation energy of the -4% film is the lowest, which is 0.456 eV. 750 -4% and PF3OV 750 The activation energies of -4% are 0.466 and 0.46 eV respectively. The activation energies of the three are lower than PV 750 -4% film activation energy (0.478 eV). By comparing the activation energy, it is found that the ionic conductivity of polymer solid electrolytes prepared using fluorinated single ion conductor polymer lithium salts is better than that of PV 750 -4% film, proving that the rational design of the single-ion conductor polymer lithium salt structure can effectively improve the ionic conductivity of the polymer solid electrolyte.

[0065] Table 1 Ionic conductivity and activation energy of polymer solid electrolytes prepared using different lithium single-ion polymer lithium salts at different temperatures

[0066] Example 4 A method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: Step 1, according to the mass fraction, 3 parts of tert-butyl mercaptan are added to 5 parts of ultrapure water and stirred evenly; a 40% mass fraction NaOH aqueous solution is dropped into the above mixed solution and fully stirred, and the system is stirred to make the pH value of the system 8; acetone (20.0 mL) is slowly added to obtain a colorless transparent solution, stirred for 0.5 h and cooled to room temperature; the above reaction is transferred to an ice bath, 3 parts of carbon disulfide, 5 parts of 2-bromopropionic acid and a 40% mass fraction NaOH aqueous solution are added, and the reaction temperature is controlled not to exceed 60°C. After the reaction stops exothermic, the ice bath is removed and the reaction is continued at room temperature for 24 h; after the reaction is completed, 5 parts of concentrated hydrochloric acid are added and the temperature is controlled to be less than 10°C to obtain a yellow oil layer and stirred until solidified, washed with a large amount of ultrapure water, and vacuum dried for 12 h to obtain a yellow solid, thereby obtaining the target product, i.e., intermediate product A; Step 2: slowly add 3 parts of sodium hydride to 10 parts of dry tetrahydrofuran under nitrogen purge, add 2 parts of polyethylene glycol monomethyl ether with a molecular weight of 750 and 1 part of 4-vinylbenzyl chloride under ice bath condition and react for 12 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water for extraction, filter and obtain the light yellow target product, recorded as VBMPEG 750 , that is, intermediate product B Step 3, 5 parts of thionyl chloride, 2 parts of sodium 4-styrenesulfonate and 6 parts of anhydrous N, N'-dimethylformamide are added to a flask, stirred in an ice bath for 0.5h, stirred at room temperature for 6h, and then frozen, filtered and evaporated to obtain styrene sulfonyl chloride. Fluorinated benzene sulfonamide, 4-dimethylaminopyridine and triethylamine are added to anhydrous oxygen-free acetonitrile, wherein the ratio of styrene sulfonyl chloride to fluorinated benzene sulfonamide, 4-dimethylaminopyridine and triethylamine is 14:8:1:10 in terms of mass fractions, and stirred for 0.5h under ice bath conditions. After the reaction is completed, an appropriate amount of anhydrous magnesium sulfate is added to the above mixed solution, dried, filtered, evaporated, and dichloromethane is removed to obtain a yellow viscous product. Finally, the product and anhydrous lithium hydroxide (mass ratio of 20:13) were dissolved in an appropriate amount of dichloromethane and stirred at room temperature for 24 hours to form a light yellow solution, thereby obtaining the target product, a fluorine-containing lithium salt monomer. The fluorine-containing benzenesulfonamide in this step is 4-fluorobenzenesulfonamide.

[0067] Step 4, according to the weight percentage, the fluorine-containing lithium salt monomer and VBMPEG 750 , azobisisobutyronitrile and BCSPA were added to 5 parts of N,N'-dimethylformamide in a ratio of 40:40:1:15, and stirred at 55-75°C for 18-24 hours. After the reaction time, the solution was poured into a large amount of anhydrous ether at -20°C to precipitate the target product. The obtained product was placed in a vacuum drying oven at 40°C and vacuum dried for 12 hours to obtain a fluorinated single-ion polymer lithium salt.

[0068] Step 5, the fluorine-containing single ion polymer lithium salt is mixed with polyethylene oxide, wherein the fluorine-containing single ion polymer lithium salt accounts for 4% of the weight of polyethylene oxide, and the crosslinking agent trimethylolpropane triacrylate is added to a round-bottom flask containing 5 parts of N,N-dimethylformamide, and heated and stirred until the mixture is completely dissolved. Then the above mixture is poured into a polytetrafluoroethylene plate, and polymerization is initiated by ultraviolet light. In the ultraviolet light polymerization layer, the light source band is 400nm, and the light intensity is 0.2wm -2 , the illumination time was 6h, and finally, it was vacuum dried at 50°C for 48h to obtain a solid electrolyte based on a single ion conductor polymer.

[0069] Example 5 A method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: Step 1, according to the mass fraction, add 3 parts of tert-butyl mercaptan to 5 parts of ultrapure water and stir evenly; drip a 50% mass fraction NaOH aqueous solution into the above mixed solution and stir thoroughly, stir the system, and make the pH value of the system 12; slowly add acetone (50.0mL) to obtain a colorless transparent solution, stir for 1.0h and cool to room temperature; transfer the above reaction to an ice bath, add 3 parts of carbon disulfide, 5 parts of 2-bromopropionic acid and a 50% mass fraction NaOH aqueous solution, control the reaction temperature not to exceed 60°C, remove the ice bath after the reaction stops exothermic, and continue the reaction at room temperature for 48h; after the reaction is completed, add 5 parts of concentrated hydrochloric acid and control the temperature to be less than 10°C to obtain a yellow oil layer and stir until solidified, wash with a large amount of ultrapure water, and vacuum dry for 15h to obtain a yellow solid, and obtain the target product, that is, intermediate product A; Step 2: slowly add 3 parts of sodium hydride to 10 parts of dry tetrahydrofuran under nitrogen purge, add 2 parts of polyethylene glycol monomethyl ether with a molecular weight of 750 and 1 part of 4-vinylbenzyl chloride under ice bath condition and react for 14 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water for extraction, filter and obtain the light yellow target product, recorded as VBMPEG. 750 , that is, intermediate product B Step 3, add 5 parts of thionyl chloride, 2 parts of sodium 4-styrenesulfonate and 6 parts of anhydrous N, N'-dimethylformamide into a flask, stir for 5 hours under ice bath conditions and 6 hours at room temperature, and then freeze, filter and evaporate to obtain styrenesulfonyl chloride. Add fluorinated benzenesulfonamide, 4-dimethylaminopyridine and triethylamine to anhydrous oxygen-free acetonitrile, wherein the ratio of styrenesulfonyl chloride to fluorinated benzenesulfonamide, 4-dimethylaminopyridine and triethylamine is 20:10:1:15 by mass, and stir for 3 hours under ice bath conditions. After the reaction is completed, add an appropriate amount of anhydrous magnesium sulfate to the mixed solution, dry, filter, evaporate, remove dichloromethane, and obtain a yellow viscous product. Finally, dissolve the product and anhydrous lithium hydroxide (mass ratio is 20:19) in an appropriate amount of dichloromethane, stir at room temperature for 36 hours to form a light yellow solution, and obtain the target product, fluorinated lithium salt monomer. The fluorine-containing benzenesulfonamide in this step is 4-trifluoromethoxy-benzenesulfonamide.

[0070] Step 4, according to the weight percentage, the fluorine-containing lithium salt monomer and VBMPEG 750 , azobisisobutyronitrile, and BCSPA were added to 5 parts of N,N'-dimethylformamide in a ratio of 50:50:1:20, and stirred at 75°C for 18 hours. After the reaction time, the solution was poured into a large amount of anhydrous ether at -20°C to precipitate the target product. The obtained product was placed in a vacuum drying oven at 60°C and vacuum dried for 6 hours to obtain a fluorinated single-ion polymer lithium salt.

[0071] Step 5, the fluorine-containing single ion polymer lithium salt is mixed with polyethylene oxide, wherein the fluorine-containing single ion polymer lithium salt accounts for 10% of the weight of polyethylene oxide, and at the same time, the crosslinking agent trimethylolpropane triacrylate is added to a round-bottom flask containing 5 parts of N,N-dimethylformamide, and heated and stirred until the mixture is completely dissolved. Then the above mixture is poured into a polytetrafluoroethylene plate, and polymerization is initiated by ultraviolet light. In the ultraviolet light polymerization layer, the light source band is 100nm, and the light intensity is 0.4wm -2 , the illumination time was 3 h, and finally, it was vacuum dried at 70 °C for 36 h to obtain a solid electrolyte based on a single ion conductor polymer.

[0072] Example 6 A method for preparing a single ion conductor polymer solid electrolyte comprises the following steps: Step 1, according to the mass fraction, 3 parts of tert-butyl mercaptan are added to 5 parts of ultrapure water and stirred evenly; a 45% mass fraction NaOH aqueous solution is dropped into the above mixed solution and fully stirred, and the system is stirred to make the pH value of the system 10; acetone (40.0 mL) is slowly added to obtain a colorless transparent solution, stirred for 0.8 hours and cooled to room temperature; the above reaction is transferred to an ice bath, 3 parts of carbon disulfide, 5 parts of 2-bromopropionic acid and a 45% mass fraction NaOH aqueous solution are added, and the reaction temperature is controlled not to exceed 60°C. After the reaction stops exothermic, the ice bath is removed and the reaction is continued at room temperature for 35 hours; after the reaction is completed, 5 parts of concentrated hydrochloric acid are added and the temperature is controlled to be less than 10°C to obtain a yellow oil layer and stirred until solidified, washed with a large amount of ultrapure water, and vacuum dried for 13 hours to obtain a yellow solid, thereby obtaining the target product, i.e., intermediate product A; Step 2: slowly add 3 parts of sodium hydride to 10 parts of dry tetrahydrofuran under nitrogen purge, add 2 parts of polyethylene glycol monomethyl ether with a molecular weight of 750 and 1 part of 4-vinylbenzyl chloride under ice bath condition and react for 13 hours. Then, rotary evaporate it, add dichloromethane and ultrapure water for extraction, filter and obtain the light yellow target product, recorded as VBMPEG 750 , that is, intermediate product B Step 3, add 5 parts of thionyl chloride, 2 parts of sodium 4-styrenesulfonate and 6 parts of anhydrous N, N'-dimethylformamide into a flask, stir for 3 hours in an ice bath and 8 hours at room temperature, and then freeze, filter and evaporate to obtain styrenesulfonyl chloride. Add fluorinated benzenesulfonamide, 4-dimethylaminopyridine and triethylamine to anhydrous oxygen-free acetonitrile, wherein the ratio of styrenesulfonyl chloride to fluorinated benzenesulfonamide, 4-dimethylaminopyridine and triethylamine is 18:9:1:13 by mass, and stir for 2 hours under ice bath conditions. After the reaction is completed, add an appropriate amount of anhydrous magnesium sulfate to the mixed solution, dry, filter, evaporate, remove dichloromethane, and obtain a yellow viscous product. Finally, dissolve the product and anhydrous lithium hydroxide (mass ratio is 20:15) in an appropriate amount of dichloromethane, stir at room temperature for 30 hours to form a light yellow solution, and obtain the target product, fluorinated lithium salt monomer. The fluorine-containing benzenesulfonamide in this step is 4-trifluoromethyl-benzenesulfonamide.

[0073] Step 4, according to the weight percentage, the fluorine-containing lithium salt monomer and VBMPEG 750 , azobisisobutyronitrile and BCSPA were added to 5 parts of N,N'-dimethylformamide in the ratio of (40~50):(40~50):1:(15~20), and stirred at 65°C for 20 hours. After the reaction time, the solution was poured into a large amount of anhydrous ether at -20°C to precipitate the target product. The obtained product was placed in a vacuum drying oven at 50°C and vacuum dried for 10 hours to obtain a fluorinated single-ion polymer lithium salt.

[0074] Step 5, the fluorine-containing single ion polymer lithium salt is mixed with polyethylene oxide, wherein the fluorine-containing single ion polymer lithium salt accounts for 6% of the weight of polyethylene oxide, and the crosslinking agent trimethylolpropane triacrylate is added to a round-bottom flask containing 5 parts of N,N-dimethylformamide, and heated and stirred until the mixture is completely dissolved. Then the above mixture is poured into a polytetrafluoroethylene plate, and polymerization is initiated by ultraviolet light. In the ultraviolet light polymerization layer, the light source band is 200 nm, and the light intensity is 0.3 wm -2 , the illumination time was 5 h, and finally, it was vacuum dried at 60 ° C for 40 h to obtain a solid electrolyte based on a single ion conductor polymer.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A single ion conductor polymer solid electrolyte, characterized in that: Its structural formula is shown in formula (V): In the formula, n is 1, and R is any one of -F, -CF3 or -OCF3.

2. A method for preparing a single ion conductor polymer solid electrolyte as described in claim 1, characterized in that: The following steps are involved: S1: Under ice bath conditions, carbon disulfide and 2-bromopropionic acid are added to tert-butyl mercaptan to obtain an intermediate product A after reaction. The structural formula of the intermediate product A is formula (I): ; In an ice bath and under nitrogen protection, polyethylene glycol monomethyl ether is reacted with 4-vinylbenzyl chloride to obtain an intermediate product B, the structural formula of the intermediate product B is formula (II): ; Styrenesulfonyl chloride is added to anhydrous oxygen-free acetonitrile, and fluorine-containing benzenesulfonamide, 4-dimethylaminopyridine and triethylamine are added, and the mixture is stirred under ice bath conditions. After the reaction is completed, the reaction product is reacted with anhydrous lithium hydroxide to obtain a fluorine-containing lithium salt monomer. The structural formula of the fluorine-containing lithium salt monomer is formula (III): Wherein, R is any one of -F, -CF3 or -OCF3; S2: adding the fluorine-containing lithium salt monomer, the intermediate product B, azobisisobutyronitrile and the intermediate product A into N,N'-dimethylformamide, stirring for reaction, and obtaining a fluorine-containing single ion polymer lithium salt; S3: adding the fluorine-containing single-ion polymer lithium salt, PEO and a cross-linking agent into N,N'-dimethylformamide, stirring until completely dissolved, and initiating polymerization by ultraviolet light to obtain the single-ion conductor polymer solid electrolyte.

3. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: In terms of mass fractions, the ratio of tert-butyl mercaptan to carbon disulfide to 2-bromopropionic acid is 3:(1-10):(5-15).

4. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: Calculated by weight, the ratio of the polyethylene glycol monomethyl ether to 4-vinylbenzyl chloride is (2-5):(1-3).

5. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: Calculated by weight, the ratio of styrenesulfonyl chloride to fluorine-containing benzenesulfonamide is (14-20): (8-10).

6. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: The fluorine-containing benzenesulfonamide is any one of 4-fluorobenzenesulfonamide, 4-trifluoromethoxy-benzenesulfonamide and 4-trifluoromethyl-benzenesulfonamide.

7. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: In terms of mass fractions, the ratio of the fluorine-containing lithium salt monomer, the intermediate product B, azobisisobutyronitrile and the intermediate product A is (40-50):(40-50):1:(15-20).

8. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: The fluorine-containing single-ion polymer lithium salt accounts for 4% to 10% of the mass of PEO.

9. The method for preparing a single ion conductor polymer solid electrolyte according to claim 2, characterized in that: In the process of initiating polymerization by ultraviolet light, the wavelength of the light source is 400-100 nm, and the light intensity is 0.2-0.4 wm -2 , the lighting time is 3~6h.

10. A lithium metal battery, characterized in that: The invention comprises a single ion conductor polymer solid electrolyte as claimed in claim 1.

Citation Information

Cited By

  • Composite solid electrolyte taking fluorinated carbon nitride as filler as well as preparation method and application of composite solid electrolyte

    CN120127231A